On the Costs of Parallel Processing in Dual-Task Performance: The Case of Lexical Processing in Word Production. - Paucke, Madlen; Oppermann, Frank; Koch, Iring; Jescheniak, Jörg D. (Journal of Experimental Psychology. Human Perception & Performance, 2015)
Previous dual-task picture-naming studies suggest that lexical processes require capacity-limited processes and prevent other tasks to be carried out in parallel. However, studies involving the processing of multiple pictures suggest that parallel lexical processing is possible. The present study investigated the specific costs that may arise when such parallel processing occurs. We used a novel dual-task paradigm by presenting 2 visual objects associated with different tasks and manipulating between-task similarity. With high similarity, a picture-naming task (Tl) was combined with a phoneme-decision task (T2), so that lexical processes were shared across tasks. With low similarity, picture-naming was combined with a size-decision T2 (nonshared lexical processes). In Experiment 1, we found that a manipulation of lexical processes (lexical frequency of Tl object name) showed an additive propagation with low between-task similarity and an overadditive propagation with high between-task similarity. Experiment 2 replicated this differential forward propagation of the lexical effect and showed that it disappeared with longer stimulus onset asynchronies. Moreover, both experiments showed backward crosstalk, indexed as worse Tl performance with high between-task similarity compared with low similarity. Together, these findings suggest that conditions of high between-task similarity can lead to parallel lexical processing in both tasks, which, however, does not result in benefits but rather in extra performance costs. These costs can be attributed to crosstalk based on the dual-task binding problem arising from parallel processing. Hence, the present study reveals that capacity-limited lexical processing can run in parallel across dual tasks but only at the expense of extraordinary high costs.